Therapeutic efficacy of atezolizumab plus bevacizumab treatment for unresectable hepatocellular carcinoma in patients with Child‐Pugh class A or B liver function in real‐world clinical practice - Tanaka, Takaaki; Hiraoka, Atsushi; Tada, Toshifumi; Hirooka, Masashi; Kariyama, Kazuya; Tani, Joji; Atsukawa, Masanori; Takaguchi, Koichi; Itobayashi, Ei; Fukunishi, Shinya; Tsuji, Kunihiko; Ishikawa, Toru; et al. (Hepatology research, 2022)
Background/Aim Atezolizumab plus bevacizumab (Atez/Bev) treatment is recommended for unresechepatocellular carcinoma (u‐HCC) patients classified as Child‐Pugh A (CP‐A). This study aimed to elucidate the prognosis of patients treated with Atez/Bev, especially CP‐A and ‐B cases. Materials/methods From September 2020 to March 2022, 457 u‐HCC patients treated with Atez/Bev were enrolled (median age 74 years, male:female = 368:89, CP‐A:CP‐B = 427:30, Child‐Pugh score [CPS] 5:6:7:8:9 = 271:156:21:8:1). Therapeutic response was evaluated using RECIST ver.1.1. Clinical features and prognosis were retrospectively evaluated. Results There were no significant differences between CP‐A and ‐B patients in regard to best response (CR:PR:SD:PD = 16:91:194:81 vs. 0:7:13:8, p = 0.739; objective response rate/disease control rate = 28.0%/78.8% vs. 25.0%/71.4%). Analysis performed using inverse probability weighting adjustments of clinical factors other than those related to hepatic reserve function with a p value < 0.10 for comparisons between patients with CP‐A and ‐B showed that the progression‐free survival (PFS) rate for CP‐A cases was better (6‐/12‐/18‐month: 58.2%/36.1%/27.8% vs. 49.6%/8.7%/non‐estimable [NE], p < 0.001), as was overall survival (OS) rate (6‐/12‐/18‐month: 89.9%/71.7%/51.4% versus 63.6%/18.4%/NE; p < 0.001). Median PFS (mPFS) and median OS (mOS) for the CPS‐5 were 9.5 months/NE, and 5.1/14.0 months for the CPS‐6 (both p < 0.001). Furthermore, for modified albumin‐bilirubin grade (mALBI)‐1/2a/2b, mPFS was 9.4/8.5/5.3 months (p < 0.001) and mOS was NE/17.8/13.4 months (p < 0.001). Conclusion Better hepatic function, such as mALBI grade 1 or 2a are thought to indicate a better condition for obtaining sufficient prognosis with Atez/Bev treatment for u‐HCC patients, whereas for CP‐B patients, who mainly shown an mALBI grade of 2b or 3, Atez/Bev might have less therapeutic efficacy.